Use of routinely collected data in reporting falls in hospitals in a local health district in New South Wales, Australia. Issue 1 (January 2017) - Trinh, Lieu Thi Thuy; Achat, Helen; Assareh, Hassan
Objective: To examine the quality of the two routinely collected sets of data, the Incident Information Management System (IIMS) and the health information exchange (HIE) in hospitals in New South Wales, Australia. Method: IIMS records indicating a fall and its location were examined. HIE data were examined using International Classification of Diseases (ICD)-10-AM codes W00-W19 and an indicator, 'onset of the condition' for falls in hospital. If onset of the condition was not recorded, ICD-10-AM code for place of occurrence (Y92.22 = Health service area) immediately following ICD-10-AM code for the fall was used. Comprehensive criteria were applied to exclude records of earlier documented falls. IIMS and HIE data were linked. Characteristics of falls that were recorded in one data set but not in the other were determined. Results: Between January 2010 and December 2014, 8647 falls in hospitals were recorded in IIMS, 2169 were recorded in HIE and 9338 were recorded in either data set (rate of 3.2 falls per 1000 bed days). IIMS captured 93% and HIE captured 23% of these falls. Of the falls recorded in HIE, 677 (31%) were not recorded in IIMS. These were more likely to be subsequent falls, by patients who were female, younger than 65 years, who underwent a non-allied health procedure or had length of stay less than 1 week. Conclusions: IIMS captured the vast majority of falls in hospitals but failed to report one-third of falls recorded in HIE.